Desenvolvimento e caracterização de células-tronco mesenquimais derivadas do tecido adiposo e seu potencial de diferenciação - Braunig, Patricia (2016)
Mesenchymal stem cells (MSCs) have demonstrated significant potential for clinical use due to their convenient isolation, lack of significant immunogenicity, lack of ethical controversy and their potential to differentiate into tissue-specific cell types. MSCs reside in almost all tissues including the adipose tissue. Adipose tissue has main advantages as wide distribution in the organism, suitable isolation and considerable amount of resident multipotent stem cells. Therefore, in this study, adipose tissue-derived mesenchymal stem cells (AT-MSCs) were isolated from BALB/c mice omentum and epididymis fat pats. During AT-MSCs maintenance and expansion in vitro, they were characterized for the expression of antigenic surface markers and for osteogenic, chondrogenic, and adipogenic differentiation potential. AT-MSCs form both sources expressed mesenchymal surface markers, CD73, and CD105 and were negative for a hematopoietic marker, CD45. The cultures derived from both adipose tissues differentiated into all three lineages. However, differences were observed in mesenchymal surface marker expression profiles as well as in the differentiation potential of AT-MSCs from different fat sources. Furthermore, AT-MSCs isolated from omentum fat depot were cultured with differentiation medium containing retinoic acid and testicular cell conditioned medium. After treatment periods, AT-MSCs showed Gdnf gene expression, this gene is a marker for Sertoli cells. The results showed that AT-MSCs from distinct fat depots have different characteristics related to stem cell surface marker expression profiles and differentiation potential.